Sex Differences in the Incidence of Peripheral Artery Disease in the Chronic Renal Insufficiency Cohort. (February 2016) - Wang, Grace J.; Shaw, Pamela A.; Townsend, Raymond R.; Anderson, Amanda H.; Xie, Dawei; Wang, Xue; Nessel, Lisa C.; Mohler, Emile R.; Sozio, Stephen M.; Jaar, Bernard G.; Chen, Jing; Wright, Jackson; et al.
Abstract : Background—: To define how the incidence of peripheral artery disease (PAD) in chronic kidney disease differs according to sex and age. Methods and Results—: The Chronic Renal Insufficiency Cohort (CRIC) is a multicenter, prospective cohort study of chronic kidney disease participants. Fine and Gray methods were used to determine the cumulative incidence of PAD, defined by an ankle brachial index <0.90 or a confirmed PAD event, with death as a competing event. Adjusted subdistribution hazard ratios from the Fine and Gray model determined the risk of PAD according to sex. A priori, we hypothesized that the relationship between sex and cumulative incidence of PAD differed according to age. The mean age of the 3174 participants in this study was 56.6 years and consisted of 55% males. During a median follow-up of 5.9 years, 17.8% developed PAD, 13.0% were lost to follow-up and 11.1% died. Females had a 1.53-fold greater adjusted PAD risk compared with males (95% confidence interval, 1.27–1.84; P <0.001). These sex-related differences in PAD risk also differed by age ( P =0.013). Women, compared with men were at a markedly increased risk for PAD at younger ages; however, at ages >70 years, the risk was similar across both the sexes. Older men had a substantially greater PAD risk compared with younger men. In women, PAD risk did not vary with age. Conclusions—: Females with chronic kidney disease have a higher PAD risk compared with males at younger ages. There is an important need to improve our understanding of the biological and clinical basis for these differences.